High-affinity reactions between antigen-specific T-cell receptors and peptides associated with allogeneic and syngeneic major histocompatibility complex class I proteins. - Sykulev, Y (1994)
We report here that the intrinsic affinities of the antigen-specific T-cell receptors (TCR) of two unrelated CD8+ T-cell clones for their respective peptide-major histocompatibility complex (MHC) ligands are higher than the values generally thought to prevail for TCR. The TCR of one clone (2C) binds an allogeneic class I MHC protein (Ld) in association with an alpha-ketoglutarate dehydrogenase nonapeptide (QLSPFPFDL, termed QL9) with an intrinsic affinity (intrinsic equilibrium association constant) of 1-2 x 10(7) M-1. The TCR of the other clone (4G3) binds a syngeneic class I MHC protein (Kb) in association with an ovalbumin octapeptide (SIINFEKL, termed pOV8) with an intrinsic affinity of 1.5 x 10(6) M-1. A comparison of the two clones, combined with current views of T-cell repertoire selection in the thymus, leads us to propose that TCR affinities are generally likely to be higher for allogeneic MHC-peptide complexes than for syngeneic MHC-peptide complexes.